Reviving the Artisan Sculptor: The Role of Ruskin, Science and Art Education - Tierney, Andrew (Four Courts Press, 2019)
On meeting the O’Sheas in Oxford Ruskin saw them as the ideal of the savage northern workmen, obstinate and generous who by natural instinct brought a fluidity, freshness and life to their work. Dr Henry Acland, instigator of the Oxford Museum, wrote of their ‘wit and alacrity’, while Ruskin referred to their ‘genius’. This energy was already apparent in their work at TCD’s Museum Building. The carving is profuse, weighty and sinuous. Tendrils spring forward from the deep undercutting, giving space to the bend of a stem or the subtle curve and dip of a leaf. They varied the tone of their work as they moved around the building: where rude imagination dominates the central bays of the north front, on the outer bays flowers and foliage appear in neatly curated rows, symmetrical, and precise.
The Museum Building of Trinity College Dublin: a model of Victorian Craftsmanship.
Keywords: Creative Arts Practice; Making Ireland; Art Education; Irish History; Sculpture; Victorian Ireland; architectural history; Culture; Education; History